Electrificación del conjunto residencial Portal del Rodeo (2022)
The following degree project is aimed at the calculations and design of the electrical system of the Portal del Rodeo Residential Complex located in the municipality of Cúcuta, North Santander Department. Made up of 4 blocks A, B, C, D, 162 apartments and 13 premises. In order to have an appropriate electrical installation, we must comply with the electrical standards and codes that guarantee an adequate development of the project.